Fever-Induced Brugada Syndrome in an Acute Gastroenteritis Patient: A Case Report - Cikutra, Rio Yansen; Irwin, Irwin (UI Scholars Hub, 2020)
Brugada syndrome (BS) is a disease caused by autosomal dominant sodium channel mutation in the heart. The prevalence of BS worldwide is estimated to be 1-5/10,000 population and the highest prevalence is in Southeast Asia which is >5/10,000 population. Brugada syndrome is a dangerous condition because it predisposes to malignant arrhythmias (ventricular tachycardia/VT and ventricular fibrillation/VS) and sudden cardiac death (SCD). Fever is a trigger for malignant arrhythmias, syncope, or SCD in BS. This article discusses about a case of 64-year-od man patient with complaint of syncope, preceded by chest pain and palpitation. The patient also had a fever and enteritis for two days. Electrocardiographic (ECG) examination was performed on the patient and a coved-type ST-segment elevation of ≥2 mm was obtained followed by a negative T wave in the right precordial leads (V1 and V2). Based on these results, the patient was diagnosed with type 1 BS. To date, the implantation of implantable cardioverter defibrillator (ICD) is the only therapy that has proven effective in preventing SCD in BS.